Scabies, a Zoonotic Disease : Present and Future Challenge - Wardhana, April H; Manurung, Joses; Iskandar, Tolibin (Indonesian Animal Sciences Society, 2006)
Scabies is a contagious skin disease caused by a mite of Sarcoptes scabiei . It is found worldwide particularly in regions related with of poverty, remote area, poor sanitations and nutritional status in both human and animals . Scabies is transmitted by direct contact . The clinical signs are intensive pruritis or itchiness, erythrema, papula and vesicle . Infestation S. scabiei caused damage skin and raised animal death (50 - 100%) while 300 millions people per year were reported to suffer from scabies . Diagnosis of scabies is based on clinical signs and confirmed with gently scrapping the skin off burrow (seeking for eggs, faecals and mites) . Beside that, the diagnosis can be obtained by ink test, mineral oil or fluorescence tetracycline test . ELISA method for detecting human scabies still has a disadvantage because there is a cross-reaction between host skin and var . S. scabiei antigens . The development of scabies vaccine also has many problems . Some human scabies cases were suspected from their livestock or pet animals . It is required a good and synergic collaboration between both health and livestock agencies that involved both human and vet medicals, investigators, quarantine staffs including researchers. Those factors become a challenge at present and in the future to prevent the spreading of scabies to a larger area and to minimize scabies cases in both human and animal, particularly in the endemic area . Â Key words : Scabies, Sarcoptes scabiei, human, animal, zoonotic